Estimating Electricity Demand: The Cost of Linearising the Budget Constraint - Maddock, Rodney; Castano, Elkin; Vella, Frank (The Review of Economics and Statistics, 1992)
This paper derives elasticity estimates for the electricity demand of a cross section of residential customers in Medellin, Colombia, where prices follow a rising block scheme. It contrasts methods following Jerry Hausman (1979, 1985) with those based on Harvey Rosen (1976). To resolve the difference between the results produced by the two methods, it uses a generalized selectivity bias corrections method due to Frank Vella (1990). Copyright 1992 by MIT Press.